Performance evaluation of photovoltaic module integrated with phase change material-filled container with external fins for extremely hot climates. (December 2020) - Kumar, Rajan; Praveen, Paidi; Gupta, Samikhshak; Saikiran, Juttu; Bharj, Rabinder Singh
Highlights: Effect of PCM along with external fins on the performance of the PV module for extremely hot climates. Tests are carried out under a continuous irradiance in indoor conditions The performance of case 3 is superior in all aspects. The reduction in the TMod is around 22.3°C and 12°C for case 3 and case 2 as compared to without cooling case. Average enhancements in the ηEl of the PV modules are around 5.16% and 6.59% for case 2 and case 3 as compared to case 1. Abstract: The present paper investigates the effect of phase change material (PCM) along with external fins on the performance of the photovoltaic (PV) module for extremely hot climates. The rise in the temperature of the PV module significantly reduces its electrical efficiency and power output. In the present research, this rise in the temperature is reduced by using PCM filled in aluminium containers with and without fins. Paraffin wax is used as PCM. The tests are carried out under an incessant irradiance in indoor conditions with the help of a solar simulator (two halogen lamps each having 500 W per module). The comparative study is performed for three cases: case 1: standalone PV module, case 2: PV module with PCM filled in an aluminium container, and case 3: PV module with PCM filled in an aluminium container having external fins at the rear of the container. The comparative analyses of the variation of the average surface temperature of the PV module, open-circuit voltage, short-circuit current, power output and efficiencies of the modules is presented. It is observed that the performance of case 3 is superior in all aspects. The reduction in the temperature of the PV module is around 22.3°C and 12°C for case 3 and case 2 as compared to without cooling case respectively. The average enhancements in the electrical efficiency of the PV modules are around 5.16% and 6.59% for case 2 and case 3 as compared to case 1, respectively.